The Impact of Property Rights on Households' Investment, Risk Coping, and Policy Preferences : Evidence from China - Deininger, Klaus; Jin, Songqing (World Bank, Washington, DC, 2014)
Even though it is widely recognized that giving farmers more secure land rights may increase agricultural investment, scholars contend that, in the case of China, such a policy might undermine the function of land as a social safety net and, as a consequence, not be sustainable or command broad support. Data from three provinces, one of which had adopted a policy to increase security of tenure in advance of the others, suggest that greater tenure security, especially if combined with transferability of land, had a positive impact on agricultural investment and, within the time frame considered, led neither to an increase in inequality of land distribution nor a reduction in households' ability to cope with exogenous shocks. Household support for more secure property rights is increased by their access to other insurance mechanisms, suggesting some role of land as a safety net. At the same time, past exposure to this type of land right has a much larger impact quantitatively, suggesting that a large part of the resistance to changed property rights arrangements disappears as household familiarity with such rights increases.